Analisis Teori Fungsionalisme Struktrual Talcott Person atas Metode Pembagian Waris Adat Berbasis Resolusi Konflik di Desa Jiken Kecamatan Tulangan, Sidoarjo - Zayad Abd Rahman; A Halil Thahir; Dewi Umi Maimunah (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2021)
This article reviews the reasons for the community and the practice of grants which are calculated as inheritance rights in Jiken Village, Tulangan District, Sidoarjo with the perspective of Talcott Parsons' Structural Functional theory.This study is important because there are many casuistic paradoxical phenomena regarding the distribution of inheritance by parents to their children before death which in the end becomes inheritance, occurs in the people of Jiken Village.This article uses a qualitative approach, the data is collected through interviews as the main instrument.The results of the study revealed that:1) The main reason for this phenomenon is the first concern of inheritance after death, there will be conflicts between heirs.Second, it is fairer if the heir himself distributes it.Third, the traditional factors that support this.2) this phenomenon is in accordance with the characteristics of the Structural Functional theory where the existence of the community agrees on the values and legal norms that apply even though they are not in accordance with the laws and regulations.However, the agreement (customary law) can bring balance, harmony, harmony and social stability that are integrated with each other.The community carried out a movement to free themselves from the distribution of inheritance that was usually used.Then the community will be in the next phase which brings the community to experience social change.